2002
DOI: 10.1007/bf03017388
|View full text |Cite
|
Sign up to set email alerts
|

The addition of hydromorphone to epidural fentanyl does not affect analgesia in early labour

Abstract: P Pu ur rp po os se e: : Epidural fentanyl after a lidocaine and epinephrine test dose, provides adequate analgesia and allows for ambulation during early labour. The current study was designed to determine the influence of hydromorphone added to an epidural fentanyl bolus (e.g., whether there is an increase in duration of analgesia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…We have successfully used epidural opioids (given as a bolus following a lidocaine-epinephrine test dose) to provide satisfactory analgesia without a significant motor block [1][2][3][4][5][6][7][8], and also have shown that an epidural infusion of bupivacaineclonidine prolongs analgesic duration [9]. There is currently a FDA "black box" warning against using epidural clonidine in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have successfully used epidural opioids (given as a bolus following a lidocaine-epinephrine test dose) to provide satisfactory analgesia without a significant motor block [1][2][3][4][5][6][7][8], and also have shown that an epidural infusion of bupivacaineclonidine prolongs analgesic duration [9]. There is currently a FDA "black box" warning against using epidural clonidine in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
“…Before this study was instituted, a power analysis was performed assuming: a standard analgesic duration of 208 ± 77 minutes an analgesia duration difference of 60 minutes; 80% power; and an alpha of 0.05 [4]. This yielded a required sample size of 54 total patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For laboring women who will be maintained on an epidural infusion containing bupivacaine with hydromorphone, four effective options to induce analgesia have been published: (1) an epidural loading bolus with hydromorphone 50-200 lg in the presence of 0.125-0.25% bupivacaine (totaling 15-30 mg) € epinephrine 1: 200,000, (2) a 3-mL epidural test dose of 1.5% lidocaine with 1: 200,000 epinephrine followed by epidural fentanyl 100 lg and hydromorphone 300 lg, (3) an intrathecal dose of bupivacaine 2.5 mg and hydromorphone 100 lg administered as part of a combined spinal-epidural procedure, and (4) an intrathecal dose of hydromorphone 40 lg followed by 3 mL of epidural 0.25% bupivacaine administered as part of a combined spinal-epidural procedure. [1][2][3][4][5][6][7][8][9] To conclude, epidural hydromorphone 100 lg might deliver rapid onset of labor analgesia, but in order to achieve this effect, it probably requires sufficient doses of coadministered local anesthetic with or without other adjuvants. Epidural 0.035% bupivacaine appears to be below the effective concentration to potentiate epidural hydromorphone when delivered as a 20-mL bolus in the active phase of labor.…”
Section: Strategies To Induce Labor Analgesia With Epidural Hydromorpmentioning
confidence: 99%